Insights into population genetics, connectivity and demographic history of the longnosed skate Dipturus oxyrinchus (Linnaeus, 1758) in the western Mediterranean Sea. Issue 1 (21st November 2019) - Melis, Riccardo; Vacca, Laura; Bellodi, Andrea; Cau, Alessandro; Porcu, Cristina; Follesa, Maria Cristina; Cannas, Rita
Abstract: Genetic information is crucial for the conservation of Dipturus oxyrinchus (Linnaeus, 1758), a threatened large skate with declining populations over most of its geographical range. The main aim of the present study was to investigate the genetic structure, connectivity and demographic history of the longnosed skate in Sardinia (western Mediterranean Sea). Patterns of population structure were assessed in 175 specimens from six sampling sites. Variation in two mitochondrial genes (cytochrome c oxidase subunit I (COI) and control region) highlighted high genetic diversity and low but significant genetic differentiation among sites, which clustered into three groups corresponding to the north‐west, north‐east and south Sardinian coasts. The observed genetic structuring could presumably depend on a combination of past geological events, contemporary restrictions to dispersal and biological characteristics of the species (e.g. site‐fidelity, no pelagic larval stage, limited dispersal of juveniles and/or adults). Demographic analyses showed signs of past population expansion, but substantial current stability of Sardinian populations. From a conservation perspective, these results are encouraging, and indicate that Sardinian populations are still large and stable, and seem not to have suffered negative side‐effects from the ever‐growing fishing pressure in the region. The occurrence of genetic structuring strongly supported the close monitoring of populations to identify any erosion of their gene pool, and high genetic variability of the Sardinian D. oxyrinchus populations could thus represent priority populations for conservation purposes, providing potential sources for recolonization in cases of local extinctions in other areas of the distribution range of the species. When the sequences from Sardinia were compared with those available from other areas, the data seem to exclude the possibility that the Atlantic and Mediterranean host totally isolated populations or even different species, as recently suggested. However, additional markers and a larger sampling sites are needed to confirm these findings.